Selling function: the advertising of sugar-containing beverages on Australian television. (10th May 2020) - Brownbill, Aimee L; Miller, Caroline L; Smithers, Lisa G; Braunack-Mayer, Annette J
Abstract: Reducing population consumption of sugar-containing beverages has become a public health priority in many countries due to causal evidence between high consumption, weight gain and non-communicable diseases. This study aims to explore how sugar-containing beverages are associated with health and wellness in television advertisements. Our sample consisted of all televised advertisements from sugar-containing beverage manufacturers aired on free-to-air television from one Australian network (four channels) in 2016 ( n = 30 unique advertisements). We transcribed advertisements for audio and visual information. We analysed data inductively using methods from thematic, discourse and multi-modal analysis. Advertisements for sugar-containing beverages reflected both traditional (physical health and reduced risk of disease) and broader (wellbeing) conceptualizations of health. Beverages were positioned in advertisements as contributing a functional role to promote and enhance health and wellbeing within the physical, mental and social domains. Beverages were advertised as correcting suboptimal states of being to achieve desirable outcomes, including relaxation, increased resistance to disease, enhanced performance, better cognitive functioning and improved social connections. Positioning beverages within a wider conceptualization of health and wellbeing aligns with how health and nutrition are increasingly being understood and sought out by consumers, creating increased opportunities for the marketing of sugar-containing beverages as 'healthy'.